Kohler's Dictionary for Accountants (Book). - Mosich, A.N.; Meyer, Philip E. (The Accounting Review, 1983)
Reviews the book "Kohler's Dictionary for Accountants," 6th ed., edited by W.W. Cooper and Yuji Ijiri.